Mother Tongue Animated Video as a Catalyst for Communication Skills among Elementary School Students - Dimas Qondias; Ruba, Yunita Rufina; Wau, Maria Patrisia; Lawe, Yosefina Uge (MIMBAR PGSD Undiksha, 2024)
Many lower-grade students have difficulty understanding lessons due to their limited proficiency in Indonesian, while they are more fluent and confident in communicating in their native language. This study aims to produce mother tongue animated videos for communication skills for second grade elementary school students. This research is a development study utilizing the ADDIE model. The research subjects include one content expert, instructional media expert, instructional design expert, one language expert, three individual test students, and 15 small group test students. Product development data were collected through questionnaires, and communication skill data were obtained through observations during product implementation. The collected data were analyzed descriptively and qualitatively. The development results of mother tongue animated videos from experts showed that the material testing result was 90% in the very good category, media expert 89% in the good category, design expert 92% in the very good category, and language expert 90% in the very good category. Meanwhile, the individual test result was 92% in the very good category, the small group test 83% in the good category, and the significant group test 80% in the good category. Observation of student communication skills during mother tongue animated video media implementation yielded 83% in the good category, 12% in the fair category, and 5% in the poor category. These results impact students' ability to express opinions, ideas, and thoughts using the language they currently master. This study recommends that mother tongue-based animated video media can shape communication skills in elementary school students.